Analysis of Socio-Economic Determinants on Infant Mortality in East Nusa Tenggara Province - Kavit, Natalia Afriyani; Sugiharti, Lilik (Jurnal Ilmu Ekonomi Terapan, 2025)
Reducing infant mortality rates remains a key focus for the government and society. Researchers conducted an analysis of socio-economic determinants of infant mortality in East Nusa Tenggara Province using panel data from 22 districts/cities from 2017 to 2023. The Random Effect Model (REM) approach was chosen after several tests. The results show that socio-economic factors, as measured by women’s education, women’s labor force participation rate, and per capita expenditure, have a significant impact on infant mortality, while access to proper sanitation and cooking fuel did not show a significant effect on infant mortality. This research can be used as a reference in formulating policies to reduce infant mortality in NTT Province, such as equalizing access to at least 12 years of education for women in each region, increasing women’s participation in the workforce and protection against wage discrimination, increasing cigarette excise along with household financial management training, monitoring and protecting household water quality, separating the kitchen area from the bedroom.